Screening of parameters for solid-state fermentation of Aspergillus niger producing cellulose using sugarcane bagasse as substrate - Jimat, Dzun Noraini; Salleh, Norhidayah; Jami, Mohammed Saedi (IIUM Press, International Islamic University Malaysia, 2018)
Microﬁbrillated cellulose (MFC) is a promising biomaterial in bionanocomposites production because of its renewable and eco-friendly properties. Conventional methods to produce MFC such as acid hydrolysis and mechanical treatment posed significant drawbacks; large amount of acid is required and increased defibrillation of alpha cellulose, respectively. Therefore, an appropriate method is very important in obtaining desired features of MFC such as high mechanical strength, high surface and low density properties. The utilization of agro-industry wastes such as sugarcane bagasse for MFC production could help to reduce the problem of lignocellulosic wastes. Thus, this study aimed to treat the sugarcane bagasse using fungal cellulases hydrolysis as a pretreatment method thus assisting the fibrillation of fiber cellulose via ultrasonication. The effects of solid-state fermentation of Aspergillus niger on cellulases activities and morphological changes of sugarcane bagasse (SCB) were investigated. Variables such as sugarcane bagasse particle size (400 and 600 µm), inoculum size (2% and 5%), medium pH (5 and 7), and fermentation time (5 and 15 days) were screened using 2-level factorial design (Design expert software, Stat-Ease Inc., Version 8.0). Analysis of variance (ANOVA) showed that the most significant parameter that affected the structural changes of sugarcane bagasse was its particle size. The increased glucose production indicated the increased of defibrillation of sugarcane bagasse. The use of fungal pretreatment through solid state fermentation of Aspergillus niger prior to ultrasonication was found to assist the later process in fibrillating sugarcane fibres. The results obtained from enzyme assays, optical microscope, SEM and FTIR showed the supporting evidence about the successful fibrillation cellulose of SCB.